2003
DOI: 10.1539/joh.45.400
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Health Effects in a Human Population Exposed to Permanent‐Waving Solution Containing Thioglycolic Acid

Abstract: higher than that before waving (3.13‰, p<0.001). The rate decreased progressively after 24 h. Our results suggest that the reproductive function of hairdressers may be affected by long-term exposure to PWS, probably due to the presence of TGA, and more attention should be paid to its potential carcinogenic effects. Hairdressers are exposed to a variety of chemicals on a daily basis, which may be absorbed, inhaled or possibly even ingested 1) . Chemical waving is the most common means of hair styling and perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 8 publications
0
24
1
Order By: Relevance
“…Workplace exposure to these chemicals causes bronchial mucosal inflammation. For example, persulfate salts cause occupational asthma and airway hyperresponsiveness via an immunological mechanism 7) . Bleach and ammonia can cause mucosal membrane irritation and are associated with occupational asthma and chronic bronchitis 8) .…”
mentioning
confidence: 99%
“…Workplace exposure to these chemicals causes bronchial mucosal inflammation. For example, persulfate salts cause occupational asthma and airway hyperresponsiveness via an immunological mechanism 7) . Bleach and ammonia can cause mucosal membrane irritation and are associated with occupational asthma and chronic bronchitis 8) .…”
mentioning
confidence: 99%
“…The percutaneous administration of TGA caused a disorder in the reproductive cycle of rats and increased the frequency of micronuclei in bone marrow cells. Taking into account these results, Gan et al (2003) recommended studies on humans that would evaluate reproductive and mutagenic problems. In a subsequent case study and control, Gan et al (2003) hairdressers in China, using a sample of 65 women between the ages of 20 and 40 years, with an average working time of 6 to 7 years and exposed constantly to straighteners, the composition of which was 12% TGA (99% purity), 8% ammonia solution, approximately 2 g sodium carbonate and 80% deionized water.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account these results, Gan et al (2003) recommended studies on humans that would evaluate reproductive and mutagenic problems. In a subsequent case study and control, Gan et al (2003) hairdressers in China, using a sample of 65 women between the ages of 20 and 40 years, with an average working time of 6 to 7 years and exposed constantly to straighteners, the composition of which was 12% TGA (99% purity), 8% ammonia solution, approximately 2 g sodium carbonate and 80% deionized water. In this study, Gan et al (2003) found anomalies in the menstrual cycle and an increase in cells with micronuclei in female hairdressers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations